Update on ischemic colitis: from etiopathology to treatment including patients of intensive care unit. (2nd August 2016) - Doulberis, Michael; Panagopoulos, Periklis; Scherz, Stephanie; Dellaporta, Erminia; Kouklakis, Georgios
ABSTRACT: Ischemic colitis is the result of colonic hypoperfusion and is regarded as a relatively rare condition. It can be roughly classified as occlusive and non-occlusive. Pathogenesis includes a usually transient compromise in the colonic vasculature, with a parallel activation of an inflammatory cascade caused primarily by reperfusion. Diagnosis of ischemic colitis remains often difficult and requires a combination of diagnostic techniques, whereas clinical signs are occasionally only seen late as complications. Gold standard is considered to be colonoscopy. Clinical presentation and treatment of ischemic colitis vary widely depending on the degree of ischemia. Patients of intensive care unit (ICU) with ischemic colitis are often under-diagnosed, since the parallel co-morbidities and the nonspecific nature of symptoms that mimic almost any abdominal pathology, can mislead the doctor. Moreover, sedated or ventilated patients can mask many of the characteristic features of ischemic colitis and make the diagnosis challenging. Bedside colonoscopy and diagnostic laparoscopy in ICUs are two options, which seem lately to be reliable and promising in diagnosing ischemic colitis in critically ill patients.